Childhood Origins of Young Adult Environmental Behavior - Evans, Gary W.; Otto, Siegmar; Kaiser, Florian G. (Psychological Science, 2018)
Prospective, longitudinal analyses revealed that over a 12-year period from ages 6 to 18, individuals who grew up with mothers with more proenvironmental attitudes engaged in more proenvironmental behavior as young adults. A similar marginal association was uncovered between mothers’ proenvironmental behaviors and the proenvironmental behavior of their young adult offspring. Maternal educational attainment, but not political ideology, was also associated with more proenvironmental behavior as children matured. Moreover, childhood time spent outdoors was positively associated with increased environmentally responsible behavior in young adulthood. Interestingly, one’s own childhood proenvironmental behavior and attitude, at least as assessed at age 6, bear little on one’s eventual proenvironmental behavior as a young adult. Finally, among this set of childhood factors, maternal education and childhood time spent outdoors were independent predictors of positive changes in environmental behavior from early childhood to young adulthood.